PENGARUH KEGIATAN PRAMUKA TERHADAP PEMBENTUKAN KARAKTER DISIPLIN PESERTA DIDIK KELAS X DI SMA NEGERI COLOMADU - Astuti, Retno Puji; Trisiana, Anita; Yusuf, Yusuf (Jurnal Global Citizen : Jurnal Ilmiah Kajian Pendidikan Kewarganegaraan, 2024)
The aim of this research was to determine whether there s an influence of scout activities on the formation of disciplined character at the tenth-grade students of SMAN Colomadu. This research is quantitative research. The population in this study was 324 students with a research sample of 36 students. The sampling technique used is proportional random sampling technique. The data collection techniques used were questionnaires, interviews and documentation. The data analysis techniques used are normality test, t test, simple linear regression test,correlation coefficient test, and coefficient of determination test with the help of SPSS statistic 25. From the statistical result using the paired sample t- test, the conclusion was obtained that the t-count value was 6.592. And when compared between t-count and t-table, dk=N-1 then 36-1=35 at a significance level of 5%. So, it could be concluded that the t-table was 2.030. Ho was rejected and Ha was accepted so that the hypothesis stated that “ there is a positive and significant influence between scout activities on the formation of disciplined character at the tenth-grade students of SMAN Colomadu”.From the results of the multiple linear regression test analysis, the regression equation was Y=16.788 + 0.668. From the analysis of the coefficient of determination, the result was 0.555, which meant that the level of effectiveness of scout activities on the character of discipline was only 0.555 or 55.5%. Meanwhile, the remaining 44.5% was influenced by other variabels .Keywords: Scout Activities, The Shaping of Disciplinary Character